Integrasi Manajemen Pendidikan dalam Pengembangan Kurikulum Pendidikan Agama Islam di Sekolah: Integration of Educational Management in the Development of Islamic Religious Education Curriculum in Schools - Minabari, Khalid Hasan; Adam, Adiyana; Bambang, Sumarni; Jaohar, Yuliyani (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
This study examines the integration of educational management in the development of Islamic Religious Education (PAI) curriculum in three senior high schools in Ternate: SMA Negeri 1 Ternate, SMA Alkhairaat Ternate, and SMA Islam Ternate. This study uses a qualitative approach with a case study design to understand the integration of educational management in the development of PAI curriculum in three senior high schools in Ternate, North Maluku. The subjects of the study included the principal, vice principal, PAI teachers, students, and school committees. Data were collected through in-depth interviews, Focus Group Discussions (FGD), participant observation, and document analysis. Data analysis was carried out using a thematic analysis approach, including data familiarization, coding, theme search, theme review, theme definition, and report writing. Data triangulation and member checking were used to increase the credibility of the study. This study revealed that the integration of educational management in the PAI curriculum in Ternate is influenced by the local context with different approaches in each school. Key findings include curriculum contextualization, school-based management, the role of stakeholders, and implementation challenges. Limitations include limited scope and short time; further research is needed. The integration of PAI education management in Ternate varies between schools, reflecting the local context. Challenges include integrating Islamic values, balancing the curriculum, and developing contextual methods.